PENDAMPINGAN MASYARAKAT DUSUN KLANDUNGAN DESA LANDUNGSARI KECAMATAN DAU KABUPATEN MALANG ATAS DAMPAK PEMBANGUNAN PENGINAPAN - Kurniawan, Kukuh Dwi; Indri Hapsari, Dwi Ratna (Jurnal Pengabdian dan Peningkatan Mutu Masyarakat (Janayu), 2021)
CSR implementation in Indonesia includes social and environmental responsibility. As felt by the people of Klandungan Hamlet, Landungsari Village, Dau District, Malang Regency, which was affected by the process of building a home stay by a commercial company in Malang Regency. There is a need for a symbiotic mutualism relationship between business actors in running their businesses and the community can also be able to carry out activities properly in the process of development and operations of the company in the future. The purpose of this service is to provide socialization and assist residents in fulfilling their rights over the development and / or operations of the company so that in the future there will be no conflicts. The method used is to accompany the negotiation meeting of the parties without taking sides, drafting the agreement until a win-win solution is reached. The result of this service is that the parties reach an agreement with the signing of a joint statement which can be used as a guide if a conflict arises.